معوقات تطبيق إدارة الجودة الشاملة بمكاتب الخدمات التعليمية من وجهة نظر مُدِيرِي المدارس الثانوية بالتعليم العام بمدينة بنغازي - القطراني خالد إقليوان; الحوتي خالد علي (Scientific Journal of University of Benghazi, 2021)
The study aimed to determine the obstacles to the application of total quality management in the offices of the educational units located within the city of Benghazi. The study also aimed to find out whether there are statistically significant differences in the responses of the study members about those obstacles from the point of view of the directors of public secondary education institutions due to the variables of gender, academic qualification and years of experience. The researcher used the descriptive approach (arithmetic averages, standard deviations, and the relative importance of all obstacles), where the researcher relied on questionnaires as a tool for the study and statistical analysis SPSS to analyze data descriptively and inferentially. The study included (55) directors. The study concluded with the most significant results; i.e. that the most prominent obstacle to the application of total quality management is that there is a lack of perception and clarity regarding the concept of total quality management among some organizational leaders. The most prominent recommendations were to enhance and develop the perceptions and knowledge of administrative leaders regarding the concepts of quality management and their comprehensive methods of application and overcoming their obstacles.